Comparación de servicios de video streaming de YouTube - Jiménez, Luis Roberto; Solera-Delgado, Marta; Toril-Genovés, Matías (My University, 2019)
YouTube is one of the most popular services on the Internet, enabling easy streaming of a video (conventional or live) with acceptable video quality. In March 2015, YouTube added 360o video streaming service which provides users with panoramic view and allows them to freely control their viewing direction during video playback. At present, the most important service in mobile networks is video streaming, which is expected to generate 82% of all IP traffic volume by 2021. Thus, understanding YouTube video and its features is the utmost importance for network operators. In this paper, a comparative study to identify the differences between the conventional and live YouTube streaming service is presented, which includes the 360o video. The analysis covers both protocol messages and application behavior. To that end, different combinations of client type (mobile phone or PC) and video service type (conventional or live) are tested. For each combination, a short video streaming session is established, where all HTTP messages (request/response) are captured and decrypted between the YouTube client and server in the video playback sequence.
Keywords: YouTube; Streaming; Comparación